Democracy and cooperation in commons management: experimental evidence of representative and direct democracy from community forests in Ethiopia. (5th December 2016) - Gatiso, Tsegaye T.; Vollan, Björn
Abstract: The authors use dynamic lab-in-the-field common pool resource experiments to investigate the role of two forms of democracy on the cooperation of forest users in Ethiopia. In this experimental setup, participants can either directly select a rule (direct democracy) or elect a leader who decides on the introduction of rules (representative democracy). These two treatments are compared with the imposition of rules and imposition of leaders. It is found that both endogenous leaders elected by the community members and endogenous rules selected by the direct involvement of the participants are more effective in promoting cooperation among the community members compared to exogenous leadership, exogenous rule imposition and the baseline scenario without any of these modifications. However, no significant difference is found between representative democracy in the election of leadership and direct democracy in the selection of rules. Leadership characteristics and behavior are further analyzed. The results underline the importance of democratic procedures.